Alih Kode dan Campur Kode dalam Tuturan Suku Pakpak di Desa Lae Motong Kecamatan Penanggalan Kabupaten Aceh Singkil - Nurhasanah Bancin; Ririn Rahayu; Radhiah Radhiah (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to describe the form of code switching and code mixing as well as the factors causing code switching and code mixing in the speech of the Pakpak tribe in Lae-Motong Village, Penanggalan District, Aceh Singkil Regency. The method used in this research is qualitative method. The results of this study found 75 conversational data containing code switching and code mixing. Code switching was found as much as 9 data in the form of internal code switching while external code switching was not found. Code mixing was found as much as 66 data in the form of inner code-mixing which is divided into 3 forms, namely: 1) 56 data in the form of words, 2) 5 data in the form of phrases, and 3) 5 data in the form of word repetition while no data was found in the form of outer code-mixing. There are 4 factors that cause code switching, namely: 1) speakers or speakers, 2) listeners or interlocutors, 3) changes in the situation or the presence of a third person, and 4) changes in the topic of conversation. The factor that causes code-mixing is the linguistic background of both speakers and their speech partners.